Malassezia-derived indoles activate the aryl hydrocarbon receptor and inhibit Toll-like receptor-induced maturation in monocyte-derived dendritic cells - Vlachos, C.a b; Schulte, B.M.a; Magiatis, P.c; Adema, G.J.a; Gaitanis, G.b (British Journal of Dermatology, 2012)
Background The aryl hydrocarbon receptor (AhR) is a nuclear receptor and transcriptional regulator with pleiotropic effects. The production of potent AhR ligands by Malassezia yeasts, such as indirubin, indolo[3,2-b]carbazole (ICZ), tryptanthrin and malassezin, has been associated with the pathogenesis of seborrhoeic dermatitis and pityriasis versicolor. Antigen-presenting cells in the skin can encounter microbes in the presence of these bioactive metabolites that could potentially modulate their function. Objectives To study the effects of the aforementioned naturally occurring ligands on AhR activation and Toll-like receptor (TLR)-induced maturation in human monocyte-derived dendritic cells (moDCs). Methods These indoles were screened for AhR activation capacity in moDCs employing CYP1A1 and CYP1B1 induction as read out and for their effects on the function of moDCs after TLR-ligand stimulation. Results Indirubin and ICZ were the most potent AhR ligands and were selected for subsequent experiments. Concurrent exposure of moDCs to indirubin or ICZ together with TLR agonists significantly augmented the AhR-mediated CYP1A1 and CYP1B1 gene expression. Additionally, mature DCs that were subsequently stimulated with AhR ligands showed increased AhR target gene expression. Moreover, these ligands limited TLR-induced phenotypic maturation (CD80, CD83, CD86, MHC II upregulation) of moDCs, reduced secretion of the inflammatory cytokines interleukin (IL)-6 and IL-12, and decreased their ability to induce alloreactive T-lymphocyte proliferation. Conclusions These results demonstrate that AhR agonists of yeast origin are able to inhibit moDC responses to TLR ligands and that moDCs can adapt through increased transcription of metabolizing enzymes such as CYP1A1 and CYP1B1. © 2012 British Association of Dermatologists.
Keywords: 2 b]carbazole; alloimmunity; aromatic hydrocarbon receptor; article; Aryl Hydrocarbon; Aryl Hydrocarbon Hydroxylases; B7 antigen; Carbazoles; CD83 antigen; CD86 antigen; Cell Aging; cell function; cell maturation; Cell Proliferation; Cells; controlled study; Cultured; Cytochrome P-450 CYP1A1; cytochrome P450 1A1; cytochrome P450 1B1; dendritic cell; Dendritic Cells; gene expression; human; human cell; Humans; indirubin; indole derivative; Indoles; indolo[3; interleukin 12; interleukin 6; Interleukin-12; Interleukin-6; major histocompatibility antigen class 2; Malassezia; malassezin; monocyte; Monocytes; nonhuman; Phenotype; priority journal; Quinazolines; Receptors; T lymphocyte; toll like receptor; toll like receptor agonist; Toll-Like Receptors; tryptanthrin; unclassified drug; upregulation